RECURRENCE RATES OF OCULAR TOXOPLASMOSIS DURING PREGNANCY - Braakenburg, Arthur M.D. (2014)
PURPOSE: To investigate whether recurrence rates of ocular toxoplasmosis are higher during pregnancy among women of childbearing age. DESIGN: Retrospective longitudinal cohort study. METHODS: We reviewed medical records of all women seen at a university eye clinic (Utrecht, Netherlands) during episodes of active toxoplasmic retinochoroiditis that occurred while the women were of childbearing age (16–42 years). Each woman was sent a questionnaire requesting information regarding all pregnancies and episodes of ocular toxoplasmosis, whether or not episodes were observed at the eye clinic. Conditional fixed-effects Poisson regression was used to model incident rate ratios of recurrence during pregnant versus non-pregnant intervals, adjusted for potential confounders, including age at time of active toxoplasmic retinochoroiditis and interval since last episode of active disease, which are known to influence risk of recurrence. RESULTS: Questionnaires were returned by 50 (58%) of 86 women, 34 of whom had 69 pregnancies during 584 person-years of study. There were 128 episodes of ocular toxoplasmosis during the study period (6 during pregnancy). First episodes of ocular toxoplasmosis occurred between ages 9.6 and 38.5 years. Youngest age at pregnancy was 16.1 years; oldest age at childbirth was 40.9 years. Incident rate ratios for pregnant versus non-pregnant intervals were in the direction of lower recurrence rates during pregnancy, with point estimates of 0.54 and 0.75 under two different approaches, but ratios were not significantly different from the null value (p-values of 0.16 and 0.55). CONCLUSIONS: Recurrence rates of ocular toxoplasmosis are likely not higher during pregnancy, in contrast to traditional beliefs.